2016
DOI: 10.1039/c5ra25197d
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity of norbornene esters in ring-opening metathesis polymerization initiated by a N-chelating Hoveyda II type catalyst

Abstract: The reactivity and activation parameters for the ROMP of eight norbornene esters in the presence of a N-chelating Hoveyda–Grubbs II type catalyst were determined. Kinetic studies prove that these parameters highly depend on the monomer structures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…The literature shows that studies on 5-norbornene-2,3-dicarboxylic ester derivatives are important for the development of new materials, which can be verified by the relevant number of recent publications. 8,[10][11][12][13] In contrast, in this study, the use of air atmosphere makes the means more robust, being a new contribution to science.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…The literature shows that studies on 5-norbornene-2,3-dicarboxylic ester derivatives are important for the development of new materials, which can be verified by the relevant number of recent publications. 8,[10][11][12][13] In contrast, in this study, the use of air atmosphere makes the means more robust, being a new contribution to science.…”
Section: Discussionmentioning
confidence: 74%
“…A study using N-chelating Hoveyda II type catalyst in the ROMP of eight of norbornene-2,3-dicarboxylic acid esters demonstrated that elongation of the aliphatic substituent affected the reactivity of esters insignificantly. 13 Discoordination of the N-Hoveyda II catalyst allows a fast approach to independent monomeric units.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The steric hindrances significantly decrease the reactivity of diesters with branching aliphatic radical under interaction with active form of ruthenium complex. In study [35], the researchers attempted to make a quantitative estimation of the initiation and growth constants. Table 5, the increase of aliphatic radical length leads to gradual increase of activation parameters.…”
Section: Correlations Inmentioning
confidence: 99%